On the Effectiveness of Using Only Eigenvalues in Structural Model Updating Problems - A.S. Nobari; D.J. Ewins (Shock and Vibration)
In this article the subject of model updating using the inverse eigensensitivity method that uses only eigenvalues in the calculation is examined. The problem of creating an underdetermined set of equations is studied and ways of preventing it are addressed.